Lucinde and the figuration of the limit: the Kantian anti-foundationalism of German Romanticism - Castillo Ávila, Antonio (Con-Textos Kantianos. International Journal of Philosophy, 2025)
This article sets out to explore, on the basis of a reading of Friedrich Schlegel's novel Lucinde, the specific philosophical position of early German Romanticism in relation to the epistemological, ethical and metaphysical controversies arising from Kantian criticism. In the context of the first generation of readers of Kant's three critiques, in which all sorts of efforts were lavished on bridging the “impassable gulf” between nature and freedom or sensible and suprasensible sphere (such as Jacobi's “salto mortale,” Reinhold's “act of consciousness,” or Fichte's “self-positioning” of the I), Schlegelian romanticism entails the uncompromising preservation of the very visibility of that gulf. Through an analysis of the compositional particularities of Lucinde's writing, this article proposes that it is through the poetic (ironic-allegorical) Darstellung of idealistic consciousness that Fruhromantik truly takes on Kant's philosophical radicality.